Prenatal Diagnosis and Perinatal Management of Gastroschisis: A Case Report - Rina Gustuti; Farah Mutiara; Yusrawati (Journal of Midwifery, 2025)
Background: Gastroschisis is a congenital abdominal wall defect characterized by herniation of abdominal organs through a paraumbilical defect without a protective membrane. Prenatal detection plays a crucial role in planning delivery and optimizing neonatal management. Case Presentation: We report a case of a 39-year-old pregnant woman, G4P2A1L2, who presented at 36–37 weeks of gestation with latent phase of labor and a history of two previous cesarean sections. Antenatal ultrasonography revealed a singleton live intrauterine fetus with suspected gastroschisis, demonstrated by herniation of fetal bowel outside the abdominal cavity without a covering membrane. Fetal well-being assessment using cardiotocography showed a category I tracing. Delivery was performed by cesarean section due to maternal obstetric indications. A male neonate was delivered with a birth weight of 2415 grams, and postnatal Ballard scoring indicated a gestational age of approximately 36 weeks. The neonate was planned for further management according to clinical condition. Conclusion: Prenatal diagnosis of gastroschisis allows for appropriate delivery planning and early neonatal management. A multidisciplinary approach involving obstetricians, neonatologists, and pediatric surgeons is essential to improve outcomes in neonates with congenital  abdominal wall defects.